The Competency Based Community Assessment: A Five Step Process - Roberts, Laura A.; Karan, Orv C. (Journal of the American Academy of Special Education Professionals, 2012)
A crucial step in the process of preparing students with disabilities for adult life is transition assessment. Using a comprehensive assessment that is built around the student’s interests, followed by assessment administration within the context of his/her community can provide special education professionals with rich data that is useful for program planning and establishing IEP goals. This article describes each step of a transitional assessment called the Competency Based Community Assessment (CBCA) which the others have found useful as a tool for creating individualized transition plans, along with program planning that is geared toward helping students with disabilities reach their full capacity in the areas of independent living, community participation and post-secondary education/employment.